ENDOSCOPIC DIAGNOSIS OF EARLY RECURRENCE IN PATIENTAS UNDERGOING SURGERY FOR LUNG CANCER - O. V. Cheremisina; M. V. Bylin; O. V. Pankova; I. G. Frolova (Сибирский онкологический журнал)
The purpose of the study: to evaluate the effectiveness of postoperative management of the bronchial stump in lung cancer patients. material and methods. Forty-four patients with stage III lung cancer underwent endoscopic examination of the bronchial tree 3, 6, 9 and 12 months after surgery. The EVIS EXERAII and LUCERA videoendoscopic complexes with consistent use of white light mode, autofluorescence and narrow- spectrum mode were used. Endoscopic results were compared with morphological findings. Results. X-ray of the chest was negative for tumor recurrence in 3 (6.8 %) cases and early metachronous tumor of the trachea was revealed in 1 (2.3 %) case. The main endoscopic symptoms of early local recurrence in the bronchial stump were the marked lilac glow identified in the AFI mode and the mucosal vascular pattern deformation Timely diagnosis of recurrence allows a special treatment to be performed.